Composite negative electrode, lithium battery and preparation method thereof
By adopting a composite structure in the negative electrode of lithium battery and using graphite and silicon materials of different specifications to control particle stacking and pore distribution, the problem of degradation of cycling and fast charging performance after graphite doping is solved, and high energy density and long cycle life are achieved Take into account both.
Patent Information
- Application Number
- CN202411713881.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-01-07
AI Technical Summary
After the existing lithium battery negative electrode material graphite increases the energy density, the circulation performance and fast charging performance are affected, making it difficult to take into account high energy density and long cycle life.
Using a composite negative electrode structure, the high aspect ratio, volume median particle size and mass ratio are controlled to form suitable particle stacks and pores by using different specifications of graphite and silicon materials in the first active layer and the second active layer respectively. Distribute to improve the energy density and cycling performance of the battery.
It effectively improves the energy density and fast charging performance of lithium batteries, while ensuring long cycle life. Through reasonable particle size and distribution regulation, the porosity and conductivity of the electrode are optimized, and the overall performance of the battery is improved.
Smart Images

Figure BDA0005156436110000081 
Figure BDA0005156436110000101 
Figure BDA0005156436110000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite negative electrode, a lithium battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the following advantages, making them an ideal energy source for modern electronic devices. First, lithium-ion batteries have a high energy density, which means they can store more energy in a relatively small volume and weight. Second, lithium-ion batteries have a long cycle life, generally up to hundreds to thousands of charge and discharge cycles. Third, lithium-ion batteries have a low self-discharge rate, so even if they are not used for a long time, the battery power loss is relatively small.
[0003] At present, the active material of the negative electrode of lithium-ion batteries is mainly graphite, which has the advantages of high electronic conductivity, large lithium ion diffusion coefficient, low lithium insertion potential, etc. Graphite is widely available and cheap, making it one of the commonly used commercial negative electrode materials. However, the capacity of graphite has reached its limit, and increasing the capacity and energy density by modifying graphite has also reached a bottleneck.
[0004] The theoretical gram capacity of graphite material is 374mAh / g; it is difficult to meet the growing energy density demand for battery cells; in order to increase the capacity, silicon is usually doped into the graphite material, but after the doping of silicon, its cycle performance and fast charging performance are greatly affected. Therefore, how to ensure high energy density while ensuring high cycle performance and fast charging performance is an urgent problem to be solved for the negative electrode of lithium batteries. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is how to ensure the cycle performance and fast charging performance of lithium batteries while adding silicon to graphite to increase the energy density; thereby providing a composite negative electrode, lithium battery and preparation method thereof to solve the above problems.
[0006] A composite negative electrode comprises a negative electrode current collector and a first active layer and a second active layer, wherein the first active layer comprises a first graphite material; and the second active layer comprises a second graphite material and a silicon material;
[0007] The aspect ratio of the first graphite material is γ1, and the volume median particle size of the first graphite material is D150, in μm, 3.3≤D150×γ1≤7.5;
[0008] The aspect ratio of the second graphite material is γ2, the volume median particle size of the second graphite material is D250, the volume median particle size of the silicon material is D350, and the ratio of the volume median particle size D350 of the silicon material to the median particle size D250 of the second graphite material is μ, α=(mass of the second graphite material / mass of the total active material) / (mass of the silicon material / mass of the total active material), 0.5≤μ×γ2×α≤2.8.
[0009] For example: the value of D150×γ1 is any value among 3.3, 3.5, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, etc., or a value not shown between any two values; the value of μ×γ2×α is any value among 0.5, 0.8, 1.0, 1.3, 1.5, 1.8, 2.0, 2.8, etc., or a value not shown between any two values.
[0010] As an implementation mode, 0.2≤γ1≤0.6; preferably, 0.2≤γ1≤0.5; for example, the value of γ1 is any value among 0.2, 0.3, 0.4, 0.5, 0.6, etc., or a value between any two values not shown;
[0011] And / or, 10≤D150≤20, preferably, 12≤D150≤18; for example, the value of D150 is any value among 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc., or a value not shown between any two values, in μm.
[0012] As an implementation mode, 0.6≤γ2≤1, preferably, 0.7≤γ2≤1; for example, the value of γ2 is any value among 0.6, 0.7, 0.8, 0.9, 1.0, etc., or a value not shown between any two values;
[0013] and / or, 5≤D250≤15, preferably, 7≤D250≤10; for example, the value of D250 is any value among 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, etc., or a value not shown between any two values, in μm;
[0014] and / or, 2≤D350≤7, preferably, 3≤D350≤6; for example, the value of D350 is any value among 2, 3, 4, 5, 6, 7, etc. or a value not shown between any two values, in μm;
[0015] and / or, 0.3≤μ≤0.8; for example, the value of μ is any value among 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc., or a value not shown between any two values;
[0016] and / or, 2.3≤α≤4; for example, the value of α is any value among 2.3, 2.5, 2.8, 3.0, 3.3, 3.5, 3.8, 4.0, etc., or a value not shown between any two values;
[0017] And / or, the mass of the second graphite material / the mass of the total active substance is 0.7-0.8; for example, the mass of the second graphite material / the mass of the total active substance is any value among 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, etc., or a value not shown between any two values;
[0018] And / or, the mass of silicon material / the mass of total active substances is 0.2-0.3; for example: the value of the mass of silicon material / the mass of total active substances is any value among 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, etc., or a value not shown between any two values.
[0019] As an embodiment thereof, the first graphite negative electrode material and the second graphite negative electrode material include one or more of artificial graphite sheets, artificial graphite blocks, modified natural flaky graphite, modified natural crystalline graphite and modified carbon-coated natural graphite blocks; preferably artificial graphite sheets, artificial graphite blocks, modified natural flaky graphite and modified natural graphite blocks.
[0020] And / or, the silicon material includes one or more of silicon-oxygen material, ball-milled silicon-carbon material, and CVD-deposited silicon-carbon material. The silicon-oxygen material includes pre-lithium silicon-oxygen material and / or pre-magnesium silicon-oxygen material. Preferably, the silicon material is pre-lithium silicon-oxygen material, pre-magnesium silicon-oxygen material, and CVD-deposited silicon-carbon material.
[0021] A method for preparing a composite negative electrode, comprising:
[0022] Preparation of negative electrode slurry: a first graphite material, a conductive material, a binder material and water are mixed and homogenized to obtain a first negative electrode slurry; a second graphite material, a silicon material, a conductive material, a binder material and water are mixed and homogenized to obtain a second negative electrode slurry;
[0023] Preparation of the first active layer: coating the first negative electrode slurry on the front and back surfaces of the negative electrode current collector to form a coating layer on the negative electrode current collector, and drying to obtain a negative electrode sheet containing the first active layer;
[0024] Preparation of the second active layer: coating the second negative electrode slurry on the first active layer, and drying to obtain a negative electrode sheet containing the first active layer and the second active layer.
[0025] In the first active layer, the first graphite material accounts for 90-95% by mass in the first active layer, the conductive material accounts for 2-5% by mass in the first active layer, and the bonding material accounts for 3-5% by mass in the first active layer;
[0026] And / or, in the second active layer, the total amount of the second graphite material and the silicon material in the second active layer accounts for 90-95% by mass, the conductive material in the second active layer accounts for 2-5% by mass, and the bonding material in the second active layer accounts for 3-5% by mass.
[0027] The conductive material includes one or more of conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotube and graphene;
[0028] And / or, the bonding material includes one or more of polyvinylidene fluoride, polyacrylic acid and styrene-butadiene latex.
[0029] A lithium battery comprises the composite negative electrode mentioned above.
[0030] The technical solution of the present invention has the following advantages:
[0031] A composite negative electrode provided by the present invention improves energy density by adding silicon material. While improving energy density, it effectively controls the aspect ratio (γ1, γ2) of graphite materials in the first active layer and the second active layer, the volume median particle size (D150, D250, D350, μ = D350 / D250) of graphite materials and silicon materials, and the coordination between the mass ratio (α), that is, controls 3.3≤D150×γ1≤7.5, 0.5≤μ×γ2×α≤2.8, to ensure the cycle performance and fast charging performance of lithium batteries. Specifically, the aspect ratio represents the ratio of the minimum Feret diameter to the maximum diameter of the particle, and is generally used to screen elongated particles or spherical particles. The lower the aspect ratio, the higher the flatness of the graphite, and the more tightly the particles are stacked, which is conducive to the preparation of high energy density electrodes; therefore, the present invention appropriately reduces the aspect ratio of the graphite particles, improves the flatness of the graphite particles, and effectively increases the energy density of the battery. At the same time, graphite particles with a lower aspect ratio exhibit high compaction density, but the porosity of the negative electrode is also significantly reduced after the particles are stacked; the study found that if the porosity of the negative electrode is too large and the compaction density is too small, the distance between particles will increase, the ion channels will increase, and the electrolyte absorption will increase, which is conducive to the rapid movement of ions; but if the distance between particles is too large, the contact probability and contact area between particles will decrease, which is not conducive to electronic conductivity, and the reduced conductivity will increase voltage polarization; therefore, suitable negative electrode porosity and pore distribution are beneficial to the fast charging and long cycle performance of the battery, and the graphite material with a specific aspect ratio and volume median particle size distribution can adjust the appropriate porosity and pore distribution to effectively ensure the fast charging and long cycle performance of the battery. Moreover, the volume median particle size of graphite has an important influence on its electrochemical performance. When the volume median particle size is high, the path for lithium ions to be embedded in the interior of graphite particles is long, the lithium ion diffusion impedance is high, and the fast charging performance is poor; when the volume median particle size is low, the specific surface area of graphite is relatively large, resulting in an increase in side reactions between graphite particles and electrolytes, and poor cycle performance; providing a moderate volume median particle size can improve fast charging performance and cycle performance. Therefore, the present invention uses silicon materials and graphite materials with high aspect ratios and small particle sizes for upper coating, and constructs an upper coating layer with better fast charging performance to inhibit lithium precipitation on the electrode surface. The silicon material has a high gram capacity, which improves the negative electrode capacity and energy density; uses a graphite material with a low aspect ratio for lower coating to increase the compaction of the pole piece; and constructs a lithium-ion battery that takes into account high specific energy, long cycle, and better fast charging performance through double-layer coating. That is, by comprehensively controlling the aspect ratio of the graphite material in the first active layer and the second active layer, the volume median particle size and mass ratio of the graphite material and the silicon material, the cycle performance and fast charging performance of the lithium battery can be guaranteed while the energy density is improved. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0034] Example 1
[0035] A composite negative electrode, the preparation process of which is as follows:
[0036] Preparation of the first active layer: Block artificial graphite is used as the first graphite material. Carbon black (Super C65) and single-walled carbon nanotubes are used as conductive agents, carboxymethyl cellulose (CMC) and styrene butadiene latex (SBR) are used as thickeners and binders, and a composite negative electrode is prepared by a traditional coating method. The negative electrode is prepared as follows: according to the above-mentioned preparation method of the composite negative electrode, a uniform slurry is obtained by mixing 90wt.% of active material, 2wt.% of conductive carbon black and 2wt.% of single-walled carbon nanotubes, 4.2wt.% of styrene butadiene latex and 1.8wt.% of carboxymethyl cellulose. The slurry is coated on the upper and lower surfaces of the copper foil, and finally placed in an oven to dry to obtain the first active layer.
[0037] Preparation of the second active layer:
[0038] Block artificial graphite is used as the second graphite material, and CVD deposited silicon carbon is used as the silicon material. Carbon black (Super C65) and single-walled carbon nanotubes are used as conductive agents, carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are used as thickeners and binders, and a composite negative electrode is prepared by a traditional coating method. The preparation of the negative electrode is as follows. According to the preparation method of the above-mentioned composite negative electrode, a uniform slurry is obtained by mixing 90wt.% of active material (of which graphite accounts for 67.5% and silicon carbon accounts for 22.5wt.%), 2wt.% of conductive carbon black and 2wt.% of single-walled carbon nanotubes, 4.5wt.% of polyacrylic acid and 1.5wt.% of carboxymethyl cellulose. The slurry is coated on the first active layer, and finally placed in an oven to dry, and then cold pressed and cut to obtain a composite negative electrode sheet.
[0039] The test methods for aspect ratio and volume median particle size are as follows:
[0040] By using a laser diffraction particle size analyzer (MS2000), the sample particles are dispersed in a liquid medium at a concentration of 200-300 mg / L, and a monochromatic light beam is passed through. After the light is scattered by the particles, it is distributed at different angles. The regular multi-element detector receives the values of the scattering diagram at many angles and records these values for analysis. Using the Rayleigh scattering formula, the scattering values are calculated to obtain the ratio of the volume of particles of each size level to the total volume, thereby obtaining the volume distribution of the particle size;
[0041] The Feret minimum diameter and maximum diameter length of the particles were obtained by using a laser diffraction particle size analyzer (MS2000), and the aspect ratio of the particles was calculated.
[0042] The aspect ratios and volume median particle sizes of the first graphite material, the second graphite material, and the silicon material in the first active layer and the second active layer in this embodiment are shown in Table 1.
[0043] Table 1
[0044]
[0045] A lithium battery, the preparation process of which is as follows:
[0046] (1) Preparation of positive electrode sheet
[0047] Commercial ternary (medium nickel / high nickel) materials are used as positive electrode active materials. Conductive carbon black (SuperC65) and conductive graphene are used as conductive agents, polyvinylidene fluoride (PVDF) and N-methylpyrrolidine (NMP) are used as binders and solvents, and the positive electrode is prepared by a traditional coating method. Mix 96wt.% of active material, 2.5wt.% of conductive agent (1.5wt% carbon black, 1wt% conductive graphene), 1.5wt.% of polyvinylidene fluoride and 37wt.% of N-methylpyrrolidine, place the mixture in a homogenizer and homogenize it twice to make the slurry completely uniform, and filter the slurry with a 200-mesh filter. Transfer the slurry with suitable viscosity to the coating machine, and coat it on both sides of the aluminum foil according to the designed coating thickness. After drying, compact and cut to obtain the positive electrode sheet.
[0048] (2) Preparation of electrolyte
[0049] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (EDC) were mixed in a volume ratio of 1:1:1, and then 1 mol / L LiPF6 was added and mixed evenly to prepare an electrolyte.
[0050] (3) Preparation of isolation membrane
[0051] A polypropylene film was used as a separator.
[0052] (4) Preparation of lithium secondary batteries
[0053] The positive electrode sheet to be assembled, the isolation film, and the negative electrode sheet to be assembled are stacked in sequence, so that the isolation film is located between the positive and negative electrode sheets to play an isolating role, and a bare battery cell is obtained; the bare battery cell is placed in a battery casing, and after drying, an electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0054] Examples 2-7 and Comparative Examples 1-4
[0055] The difference between Examples 2-7 and Comparative Examples 1-4 and Example 1 is that the parameter specifications of the first graphite material in a composite negative electrode are different. Specifically, the values of the aspect ratio γ1 of the first graphite material and the volume median particle size D150 of the first graphite material in Examples 2-7 and Comparative Examples 1-4 are shown in Table 2 below.
[0056] Table 2
[0057] <![CDATA[Aspect ratio γ1]]> <![CDATA[D150 / μm]]> <![CDATA[D150×γ1]]> Example 2 0.45 15 6.75 Example 3 0.36 14 5.04 Example 4 0.5 14 7 Example 5 0.45 14 6.3 Example 6 0.25 18 4.5 Example 7 0.55 12 6.6 Comparative Example 1 0.4 5 2 Comparative Example 2 0.4 30 12 Comparative Example 3 0.1 15 1.5 Comparative Example 4 0.8 15 12
[0058] Except for the parameter conditions in Table 2 above, the other parameter conditions used in Examples 2-7 and Comparative Examples 1-4 are the same as those in Example 1.
[0059] Examples 8-16 and Comparative Examples 5-9
[0060] The difference between Examples 8-16 and Comparative Examples 5-9 and Example 5 is that the parameter specifications of the second active layer in a composite negative electrode are different. Specifically, the aspect ratio γ2 of the second graphite material of Examples 8-16 and Comparative Examples 5-9, the volume median particle size D250 of the second graphite material, the volume median particle size D350 of the silicon material, and the proportion coefficient (α) = (mass of the second graphite material / mass of the total active substance) / (mass of the silicon material / mass of the total active substance) are shown in Tables 3-4 below.
[0061] Table 3
[0062]
[0063] Table 4
[0064] Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 <![CDATA[Aspect ratio (γ2) > 0.2 0.8 0.8 0.8 0.8 <![CDATA[Volume median particle size (D250) / μm]]> 8 4 20 8 8 <![CDATA[Volume median particle size (D350) / μm]]> 4 10 4 4 4 Median particle size ratio μ 0.5 2.5 0.15 0.5 0.5 Second graphite material mass ratio 0.75 0.75 0.75 0.3 0.9 Silicon material mass ratio 0.25 0.25 0.25 0.7 0.1 <![CDATA[Percentage coefficient (α) > 3 3 3 0.4 9 μ×γ2×α 0.3 6 0.36 0.16 3.6
[0065] Except for the parameter conditions in Table 3 and Table 4 above, the other parameter conditions used in Examples 8-16 and Comparative Examples 5-9 are the same as those in Example 5.
[0066] Experimental example
[0067] The performance of the lithium batteries prepared in the examples and comparative examples was tested, and the specific testing method is as follows:
[0068] (1) Electrolyte retention coefficient test:
[0069] At 25°C, the unfilled lithium secondary batteries prepared in the examples and comparative examples were weighed (m1) and recorded. After the liquid filling operation and waiting for the battery to stand (electrolyte infiltration) was completed, the battery was subjected to liquid absorption and final sealing operation and weighed (m2) and recorded. The battery was formed and divided into different capacities, and the actual capacity (C) of each battery cell was recorded. The liquid retention coefficient of the lithium secondary batteries prepared in the examples and comparative examples was calculated and compared by the formula (m2-m1) / C*100%.
[0070] (2) Dynamic performance test:
[0071] At 25°C, the lithium secondary batteries prepared in the examples and comparative examples were fully charged and discharged at a 3C rate until the capacity of the lithium secondary batteries decayed to 80% of the initial capacity, the number of cycles was recorded, and then the negative electrode plates were disassembled and the lithium deposition on the surface of the negative electrode plates was observed. Among them, the area of lithium deposition on the surface of the negative electrode plates is less than 5%, which is considered to be slight lithium deposition, the area of lithium deposition on the surface of the negative electrode plates is 5% to 40%, which is considered to be moderate lithium deposition, and the area of lithium deposition on the surface of the negative electrode plates is greater than 40%, which is considered to be severe lithium deposition.
[0072] (3) Cyclic performance test:
[0073] At 25° C., the lithium secondary batteries prepared in the examples and comparative examples were charged and discharged at a rate of 1C, and full charge and discharge cycle tests were performed until the capacity of the lithium secondary batteries decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0074] (4) 45℃, 1C cycle test:
[0075] At 45° C., the lithium secondary batteries prepared in the examples and comparative examples were charged and discharged at a rate of 1C, and full charge and discharge cycle tests were performed until the capacity of the lithium secondary batteries decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0076] (5) Actual energy density test:
[0077] At 25°C, the lithium ion batteries prepared in the embodiments and comparative examples were fully charged at a 1C rate and fully discharged at a 1C rate, and the actual discharge energy at this time was recorded; at 25°C, the lithium ion batteries were weighed using an electronic balance; the ratio of the actual discharge energy of the lithium ion battery at 1C to the weight of the lithium ion battery is the actual energy density of the lithium ion battery, in units of Wh / kg.
[0078] The test results of the embodiments and comparative examples are shown in Tables 5 and 6 below.
[0079] Table 5
[0080]
[0081] Table 6
[0082]
[0083] It can be seen from the data in the above table that when the parameters of the first active layer and the second active layer in the negative electrode of the present invention are within the above-mentioned range of values, the energy density, kinetic performance and cycle performance of the lithium-ion battery are better. This is due to the suitable particle flatness and particle size ratio of the first graphite material in the first active layer provided by the present invention, and the particles are compacted tightly, which improves the energy density and high temperature performance of the battery cell. The suitable particle sphericity, particle size ratio and material amount ratio of the second graphite material and the silicon material in the second active layer provided improve the energy density and fast charging performance of the battery cell. The constructed negative electrode has higher specific energy and better electrochemical properties.
[0084] In the above-mentioned comparative example 1, when the median particle size of the first graphite material in the first active layer is too low, resulting in γ1×D150 exceeding the lower limit, the negative electrode coating of the lithium-ion battery is difficult. This is because the viscosity of the slurry becomes larger when the graphite particle size is too small, which is not conducive to increasing the solid content and increases the difficulty of coating; the energy density of the battery cell is reduced and the high-temperature cycle performance and normal-temperature cycle performance are deteriorated. This is because the small graphite particle size leads to reduced compaction of the first active layer, and the small graphite particle size leads to increased side reactions. Although it helps the rate performance, the high-temperature performance is significantly deteriorated.
[0085] In the above comparative example 2, the median particle size of the first graphite material in the first active layer is too high, resulting in γ1×D150 exceeding the upper limit, and severe lithium deposition occurs at the negative electrode interface after the lithium-ion battery is disassembled. This is because when the median particle size of graphite is too large, the van der Waals force that lithium ions need to overcome when embedding into graphite is greater, and the embedding is more difficult, resulting in obvious polarization and lithium deposition at a higher current density.
[0086] In the above comparative example 3, when the aspect ratio of the first graphite material in the first active layer is too small, resulting in γ1×D150 exceeding the lower limit, the negative electrode disassembly interface of the lithium-ion battery after the fast charge test also showed serious lithium deposition, and the cycle life also showed obvious attenuation. This is because the aspect ratio of graphite is small, the compaction is improved but the electrode pores are compressed, resulting in difficulty in electrolyte infiltration and a low liquid retention coefficient, which affects the long cycle performance and fast charge performance of the battery cell.
[0087] In the above comparative example 4, when the aspect ratio of the first graphite material in the first active layer is too small, resulting in γ1×D150 exceeding the upper limit, the lithium-ion battery exhibits a lower energy density. This is because the aspect ratio of the lower graphite layer is large, the compaction density is significantly reduced, and the energy density decreases.
[0088] In the above-mentioned comparative example 5, when the aspect ratio γ2 of the silicon material of the second graphite material in the second active layer is too low, resulting in μ×γ2×α exceeding the lower limit, the lithium-ion battery suffers from severe lithium plating, and the high-temperature and room-temperature cycle performances deteriorate. Because the graphite and silicon particles are too flat and the pores are small, which is not conducive to the infiltration of the electrolyte, the lithium-ion transmission performance is reduced, resulting in severe lithium plating.
[0089] In the above-mentioned comparative example 6, when the median particle size of the second graphite material in the second active layer is too small and the median particle size of the silicon material is too large, the particle size ratio (μ) is too large, so that μ×γ2×α exceeds the upper limit, and the lithium-ion battery has serious lithium deposition and the cycle test deteriorates seriously. This is because the silicon particles are too large and the graphite particles cannot effectively inhibit the volume expansion of the silicon material. As the cycle progresses, the volume expansion is large, resulting in particle breakage and an increase in the distance between particles. On the one hand, the electron transmission capacity between particles is reduced, resulting in lithium deposition. On the other hand, the active material is broken, resulting in an increase in side reactions and a decrease in cycle stability.
[0090] In the above comparative example 7, when the median particle size of the second graphite material in the second active layer is too large and the median particle size of the silicon material is too small, the particle size ratio (μ) is too small, so that μ×γ2×α exceeds the lower limit, and the lithium-ion battery has serious lithium deposition and deterioration in high-temperature cycle tests. This is because the silicon material particle size is too small, the electrical contact with the graphite is reduced, and the rate performance is poor; and the silicon material particle size is too small, which leads to increased side reactions and significantly deteriorated high-temperature performance.
[0091] In the above comparative example 8, when the mass ratio of the second graphite material in the second active layer is too small and the mass ratio of the silicon material is too large, the ratio of the proportion coefficient (α) is too small, so that μ×γ2×α exceeds the lower limit, and the lithium battery shows a very high energy density, but serious lithium deposition occurs on the surface and the cycle performance deteriorates seriously. This is because the silicon material content is too large. Although the energy density is significantly improved, the silicon material rate performance is poor, resulting in serious lithium deposition; after a long cycle, the silicon material expands greatly and is easy to break, resulting in serious deterioration of long cycle performance and high temperature performance, which poses a safety risk.
[0092] In the above comparative example 9, when the mass ratio of the second graphite material in the second active layer is too large and the mass ratio of the silicon material is too small, the ratio of the proportion coefficient (α) is too large, so that μ×γ2×α exceeds the upper limit, and the lithium-ion battery exhibits good electrochemical performance, but the energy density is too low. This is because the silicon content is too low and the specific capacity of graphite is low, resulting in a low battery energy density.
[0093] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A composite negative electrode, characterized in that: It comprises a negative electrode current collector and a first active layer and a second active layer, wherein the first active layer comprises a first graphite material; and the second active layer comprises a second graphite material and a silicon material; The aspect ratio of the first graphite material is γ1, and the volume median particle size of the first graphite material is D150, in μm, 3.3≤D150×γ1≤7.5; The aspect ratio of the second graphite material is γ2; the volume median particle size of the second graphite material is D250, and the volume median particle size of the silicon material is D350; the ratio of the volume median particle size D350 of the silicon material to the volume median particle size D250 of the second graphite material is μ, α=(mass of the second graphite material / mass of the total active material) / (mass of the silicon material / mass of the total active material), 0.5≤μ×γ2×α≤2.
8.
2. The composite negative electrode according to claim 1, characterized in that 0.2≤γ1≤0.6; And / or, 10≤D150≤20.
3. The composite negative electrode according to claim 2, characterized in that: 0.2≤γ1≤0.5; And / or, 12≤D150≤18.
4. The composite negative electrode according to any one of claims 1 to 3, characterized in that: 0.6≤γ2≤1, preferably, 0.7≤γ2≤1; and / or, 5≤D250≤15, or, 7≤D250≤10, in μm; and / or, 2≤D350≤7, or, 3≤D350≤6, unit: μm; and / or, 0.3≤μ≤0.8; and / or, 2.3≤α≤4; and / or, the mass of the second graphite material / the mass of the total active material is 0.7 to 0.8; And / or, the mass of silicon material / the mass of total active substances is 0.2 to 0.
3.
5. The composite negative electrode according to any one of claims 1 to 4, characterized in that: The first graphite negative electrode material and the second graphite negative electrode material include one or more of artificial graphite sheets, artificial graphite blocks, modified natural flaky graphite, modified natural crystalline graphite and modified carbon-coated natural graphite blocks; And / or, the silicon material includes one or more of silicon-oxygen material, ball-milled silicon-carbon material, and CVD-deposited silicon-carbon material.
6. The composite negative electrode according to claim 5, characterized in that: The silicon-oxygen material includes a pre-lithium silicon-oxygen material and / or a pre-magnesium silicon-oxygen material.
7. The method for preparing the composite negative electrode according to any one of claims 1 to 6, characterized in that: include: Preparation of negative electrode slurry: mixing a first graphite material, a conductive material, a bonding material and water to obtain a first negative electrode slurry; Mixing a second graphite material, a silicon material, a conductive material, a bonding material and water to obtain a second negative electrode slurry; Preparation of the first active layer: coating the first negative electrode slurry on the front and back surfaces of the negative electrode current collector to form a coating layer on the negative electrode current collector, and drying to obtain a negative electrode sheet containing the first active layer; Preparation of the second active layer: coating the second negative electrode slurry on the first active layer, and drying to obtain a negative electrode sheet containing the first active layer and the second active layer.
8. The preparation method according to claim 7, characterized in that: In the first active layer, the first graphite material accounts for 90-95% by mass in the first active layer, the conductive material accounts for 2-5% by mass in the first active layer, and the bonding material accounts for 3-5% by mass in the first active layer; And / or, in the second active layer, the total amount of the second graphite material and the silicon material in the second active layer accounts for 90-95% by mass, the conductive material in the second active layer accounts for 2-5% by mass, and the bonding material in the second active layer accounts for 3-5% by mass.
9. The preparation method according to claim 7 or 8, characterized in that: The conductive material includes one or more of conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotube and graphene; And / or, the bonding material includes one or more of polyvinylidene fluoride, polyacrylic acid and styrene-butadiene latex.
10. A lithium battery, characterized in that: A composite negative electrode comprising any one of claims 1 to 6.